Analysis of the essence, structure and features of educational process in modern pedagogical practice of higher education establishments - Молчанюк, О. В.; Борзик, О. Б. (Scientific notes of the pedagogical department, 2018)
The article deals with the essence, structure and functions of educational process in modern pedagogical practice of higher education establishments. The process of updating education content is established to be an objective natural consequence of science evolution as a whole and individual sectors in accordance with the pace of scientific-technical progress. The concept "education" is defined and the aim of modern education is revealed. The comparative analysis of traditional, developing and personality-oriented types of educational process is conducted. The features of organizing educational process at higher education establishments due to traditional, developing and personality-oriented training is highlighted. Advantages and disadvantages of each type of organizing educational process are characterized. It is proven that education content, forms, methods, while maintaining the traditional for modern society goals, however contradict new trends focused on humanistic goals. With traditional training, students master knowledge, skills, get socialized, disciplined. However, the educational process type is marked by narrow specialization, formal mastering of knowledge. In addition, there is unification, averaging of tutor-student personality, further difficulties in the process of independent mental activity. The essence of developing learning lies in the fact that a personality does not only master certain knowledge and skills, but also acquires ways of action. In this case, the student acts as a subject of academic activities, independently defining goals and ways of achievement, asks tutors questions of the problematic nature. The tutor, in her turn, creates training activities with students, based on interpersonal relationships. It is established that when forming educational process on the principle of personality-oriented training, the student is developing as a unique personality. With such principle, there is sense of psychological security, joy, trust; gradually a personality acquires abilities to solve everyday problems. As a result of subject- subject relationship of tutor and student, interpersonal relationships are built. It is established that despite the fact that the majority of modern educational establishments are oriented to traditional learning, there are more and more universities that are oriented to developing and personality-oriented trainingwhen implementing educational process. Theoretical analysis of scientific literature on the defined issue proves that the formation of educational content in terms of the systemic approach should be based on a thorough analysis of training goals and diagnosis of the acquired at the previous level of the student’s learning experience to detalize orientation content of education using  pre-defined learning objectives.